Quantitative testing method for curing degree of road polyurethane mixture
By measuring the content of NCO functional groups and benzene rings in the polyurethane mixture and calculating the curing degree, the problem that the curing degree in the prior art cannot be accurately evaluated, and a rapid and quantitative evaluation effect is achieved.
Patent Information
- Application Number
- CN202411647673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art cannot accurately and quantitatively evaluate the degree of curing of polyurethane mixtures, resulting in low evaluation efficiency and inaccurate results.
By measuring the content of NCO functional groups and the content of benzene ring in the polyurethane mixture, the content index A of the NCO functional groups was calculated, and the degree of curing was calculated using formula (1) to achieve quantitative testing.
This method can quickly and accurately evaluate the degree of curing of polyurethane mixtures, improve evaluation efficiency, and reduce deviations due to instrument errors.
Smart Images

Figure CN119804760A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials, and in particular to a quantitative testing method for the curing degree of a road polyurethane mixture. Background Art
[0002] Polyurethane is one of the key synthetic materials developed in the world today. It has attracted wide attention due to its excellent properties such as high adhesion, high elasticity and chemical corrosion resistance. Its chemical composition, molecular structure and macroscopic performance have a great control threshold. It can be widely used in various engineering fields in different material types such as elastomers, foams, adhesives, coatings, sealants, etc. It not only has good mechanical, bonding, water damage resistance, chemical stability and other properties, but also has the advantages of stable performance, low energy consumption and suitable mixing at room temperature. Therefore, the diverse material types and excellent performance of polyurethane provide greater possibilities for subsequent promotion.
[0003] Polyurethane mixture is a road building material that uses polyurethane adhesive as a binder to completely replace asphalt and is mixed with sand and gravel materials at room temperature. Compared with asphalt pavement, it has significant green, low-carbon and high-performance advantages. This technology is a disruptive scientific and technological innovation carried out in the field of road engineering in my country in recent years, and is expected to revolutionize the road material technology system over the past century.
[0004] Polyurethane mixtures are significantly affected by the curing characteristics of polyurethane adhesives. The mechanical strength of polyurethane mixtures will gradually increase with the extension of curing time. This is essentially the reaction between the NCO groups inside the polyurethane and water. In this process, the polyurethane mixture gradually solidifies, the strength of the intermolecular force gradually increases, and the mechanics of the mixture gradually increases on a macro scale. This shows that the degree of curing of the polyurethane mixture not only has an important influence on its mechanical strength, but also has an important influence on the timing of the polyurethane pavement opening to traffic and its later durability. Therefore, it is extremely important to accurately judge the degree of curing of the polyurethane mixture.
[0005] At present, there are two main methods for evaluating the curing degree of polyurethane mixtures: empirical method and mechanical method. The empirical method is to judge the curing degree by observing the color of the cross section of the polyurethane mixture based on experimental experience. It is difficult to observe subtle changes in color with the naked eye, so it is difficult to accurately evaluate its curing degree, and it is impossible to quantitatively evaluate the curing degree of the polyurethane mixture; the mechanical method is to judge the curing degree of the polyurethane mixture based on the relationship between the stability and time through the Marshall stability test. The above method is relatively cumbersome and it is difficult to accurately judge the curing stage of the polyurethane mixture. At the same time, the stability experiment uses the pressure value when the specimen is damaged as the stability value, and judges the curing degree of the polyurethane mixture and whether the curing is completed based on the stability value, and then estimates the curing degree based on the pressure value, which cannot directly and accurately evaluate the curing degree of the polyurethane mixture. Summary of the invention
[0006] The present invention provides a quantitative testing method for the curing degree of a road polyurethane mixture, which is used to solve the defect that the curing degree of a polyurethane mixture cannot be quantitatively measured or cannot be directly quantitatively and accurately evaluated in the prior art, and realizes rapid and quantitative evaluation of the curing degree of the polyurethane mixture. Moreover, on the basis of accurately evaluating the curing degree of the polyurethane mixture, the present invention can not only improve the evaluation efficiency of the curing degree of the polyurethane mixture, but also has important significance for the promotion of polyurethane materials in road engineering.
[0007] The present invention provides a quantitative test method for the curing degree of a road polyurethane mixture, comprising obtaining the content of NCO functional groups and the content of benzene rings in the polyurethane mixture, and calculating the content index A of the NCO functional groups, wherein the content index A of the NCO functional groups refers to the relative content of the NCO functional groups relative to the benzene rings in the polyurethane mixture, that is, the content index A of the NCO functional groups = the content of the NCO functional groups / the content of the benzene rings, and the calculation formula of the curing degree is: Curing degree = (1-A1 / A0) × 100% Formula (1), In formula (1), A0 represents the content index of the initial NCO functional group of the road polyurethane mixture before curing; A1 represents the content index of the NCO functional group at the test time after the road polyurethane mixture starts to cure.
[0008] The essence of the curing of polyurethane mixture is the curing of polyurethane adhesive. The NCO group inside the polyurethane reacts with water. In this process, the polyurethane mixture gradually solidifies and the strength of the intermolecular force gradually increases. During the curing process, the content of the NCO functional group will gradually decrease as the degree of curing increases. Therefore, the quantitative test method of calculating the degree of curing of the polyurethane mixture by calculating the reduction of the NCO functional group proposed by the present invention based on the curing reaction mechanism of the polyurethane mixture can accurately, quantitatively and directly evaluate the degree of curing of the polyurethane mixture.
[0009] Due to equipment errors, evaluating the curing degree of the polyurethane mixture simply by the change in NCO content may result in large errors. Therefore, the present invention reflects the current NCO functional group content by calculating the ratio of the NCO functional group content to the benzene ring content, which can more accurately evaluate the curing degree of the polyurethane mixture.
[0010] In some embodiments of the present invention, the quantitative testing method comprises the steps of: (1) Determine the test section and, based on the Marshall test, determine the location where the specimen fails, which is determined as the location of the test section farthest from the center section of the specimen; if the specimen fails at multiple locations during the Marshall test, the locations of the test sections on both sides of the second section shall not exceed the failure location closest to the center of the specimen; (2) Selecting test points on the test section; (3) Sampling is performed at each test point for analysis to obtain the content of NCO functional groups and the content of benzene rings; (4) Calculate the curing degree of each test point using formula (1); (5) Calculate the overall degree of curing for each test section; (6) Calculate the degree of curing of the specimen.
[0011] In order to make the evaluation result more accurate, in step (1), the central section of the specimen is taken as the second section, and at least three sections are selected as test sections, wherein the at least three sections include the second section and the test sections on both sides thereof. Preferably, the test sections on both sides of the second section are symmetrically distributed about the second section.
[0012] In some embodiments of the present invention, the spacing between adjacent test sections is preferably 0.5-2.5 cm. The spacing between adjacent test sections is adjusted according to the mixture gradation, and the adjustment principle is that the larger the gradation, the larger the section spacing.
[0013] Considering the problem of uneven curing degree of polyurethane mixture, combined with the stress characteristics of Marshall stability test, at least three sections are selected in the middle and left and right sides of the specimen. The section spacing should be adjusted according to the gradation. The adjustment principle is that the larger the gradation, the larger the section spacing. The curing degree of at least three sections is evaluated respectively, and the curing degree of polyurethane mixture is obtained on this basis. This test method can achieve the purpose of horizontal comparison of different evaluation results, and improve the applicability and accuracy of the test method.
[0014] In some embodiments of the present invention, 3-7 test sections are selected, including the second section and the first section and the third section on both sides thereof, or, further including the fourth section and the fifth section on both sides of the second section, or, further including the sixth section and the seventh section on both sides of the second section. Preferably, 3-5 test sections are selected. Preferably, the number of the test sections is an odd number.
[0015] Preferably, each of the test points should be selected in the polyurethane adhesive area as much as possible to exclude interference from materials such as stones, so that the degree of curing obtained is more accurate.
[0016] In order to further make the evaluation results more accurate, 3-9 points are selected from the test section as test points; preferably, 4-9 test points are selected from each test section; more preferably, 6-9 test points are selected from each test section.
[0017] The more test sections are selected and the more test points are selected on each section, the more accurate the final curing degree will be and the closer it will be to the actual curing degree of the polyurethane mixture.
[0018] Preferably, in step (5), the average degree of solidification of all test points of each test section is calculated and recorded as the overall degree of solidification of the test section as L n , n corresponds to the test section name.
[0019] Preferably, in step (6), firstly, the average degree of solidification of the test section symmetrical to the second section is calculated, denoted as L nn If a test section does not have a symmetrical test section, the overall curing degree L n Denoted as L fn , where n corresponds to the test section name; then, calculate L2, L nn , L fn The average value of is taken as the final curing degree of the road polyurethane mixture.
[0020] If there are four test sections: the second section in the middle of the specimen, the first section, the third section, and the fourth section symmetrically distributed about the second section. In the above curing degree result processing process, the single-point curing degree of each test point is first calculated, and then the average curing degree of all test points in the same test section is taken as the overall curing degree of the section, recorded as L1, L2, L3 and L4 Then calculate the average curing degree of two sections with similar curing degree, that is, calculate the average value of L1 and L3, as the average curing degree L of the first section and the third section 13 Since there is no test section symmetrically distributed with the fourth section, its overall curing degree L4 is recorded as L f4 Finally, take L2, L 13 , L f4 The average value is used as the final reliable curing degree L of the polyurethane mixture. 1234 .
[0021] Taking three sections as test sections as an example, the test sections include the second section in the middle of the specimen, the first section and the third section symmetrically distributed about the second section. First, according to the peak area of the NCO functional group and the benzene ring in the infrared spectrum, the single-point curing degree can be calculated, so that the overall curing degree L1 of the first section, the overall curing degree L2 of the second section and the overall curing degree L3 of the second section can be calculated, and then the average value of the curing strength L1 of the first section and the overall curing strength L3 of the third section is calculated as the average curing degree of the first section and the third section, recorded as L 13 , and then calculate the overall curing strength L2 and L 13 The average value of is taken as the curing degree of the polyurethane mixture, denoted as L 123 , L 123 It is an accurate and reliable indicator of the degree of curing of the polyurethane mixture.
[0022] In the above result processing process, the average curing degree of two test sections with similar curing degrees is first calculated, and finally averaged with the curing degree of other test sections, so that the result obtained is more accurate.
[0023] Preferably, the content of the NCO functional group and the content of the benzene ring can be obtained by a quantitative analysis method, preferably the quantitative analysis method includes but is not limited to nuclear magnetic resonance spectroscopy (NMR) and infrared spectroscopy (FTIR). For example, infrared spectroscopy is used for quantitative analysis, and the current NCO functional group index is obtained by calculating the ratio of the peak area of the NCO functional group to the peak area of the benzene ring, and then the degree of curing can be calculated by formula (1).
[0024] The test method of the present invention is proposed based on the curing mechanism of the polyurethane mixture. The content of NCO functional groups and the content of benzene rings in the polyurethane are obtained by a quantitative analysis method, and the content of NCO functional groups is further reflected by the ratio of the content of NCO functional groups to the content of benzene rings. The curing degree of the polyurethane mixture is further calculated by formula (1), thereby achieving a direct, quantitative and accurate evaluation of the curing degree of the polyurethane mixture, while avoiding the deviation caused by instrument error, and the result is more accurate.
[0025] Furthermore, considering that the polyurethane mixture may have uneven curing degree, combined with the stress characteristics of the Marshall stability test, at least three sections are selected in the middle and left and right sides of the specimen. The section spacing should be adjusted according to the gradation. The adjustment principle is that the larger the gradation, the larger the section spacing. The curing degree of at least three sections is evaluated respectively, and the curing degree of the polyurethane mixture is obtained on this basis. This test method can achieve the purpose of horizontal comparison of different evaluation results, and improves the applicability and accuracy of the test method. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is one of the Fourier infrared spectra of the uncured AC-13 graded polyurethane mixture according to the quantitative test method of the curing degree of the road polyurethane mixture provided by the present invention.
[0028] Figure 2 It is one of the test section selection schematic diagrams of the quantitative test method for the curing degree of the road polyurethane mixture provided by the present invention.
[0029] Figure 3 It is one of the schematic diagrams for selecting test points on a test section of a quantitative test method for the degree of curing of a road polyurethane mixture provided by the present invention.
[0030] Figure 4 This is one of the result diagrams for judging the curing degree of road polyurethane mixture according to the empirical method.
[0031] Figure 5 This is the second result of judging the curing degree of road polyurethane mixture according to the empirical method.
[0032] Figure 6 This is one of the result graphs of the stability test for judging the degree of curing of road polyurethane mixtures using the mechanical method.
[0033] Figure 7 is based on Figure 6 One of the result graphs showing the degree of curing of the road polyurethane mixture obtained from the results of the stability test.
[0034] Reference numerals: A: first section, B: second section, C: third section; 1-9: test points 1-9; A1, A2, A3: longitudinal quarters; H1, H2, H3: transverse quarters. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The Fourier transform infrared (FT-IR) analysis method used in the present invention is: using German Bruker TENSOR27 infrared spectrometer for evaluation. KBr tablet or smear, scanning times: 16 times, wave number range: 4000~500cm -1 , resolution: 2cm -1 .
[0037] Example 1 A quantitative testing method for the curing degree of a road polyurethane mixture comprises the following steps.
[0038] (1) Prepare a polyurethane mixture with AC-13 grading and a Marshall specimen, and take the mixture for Fourier infrared evaluation before curing to obtain an infrared spectrum, such as Figure 1 The characteristic functional group of polyurethane is the NCO group, and the peak transmittance of this group in the FTIR spectrum is located at 2270 cm -1 , so we choose 2420 cm -1 -2120 cm -1 The peak area of the NCO functional group is calculated in the vicinity; the peak of the benzene ring is located at 1596cm -1 When the material is not cured, the peak area of the NCO functional group is 28.839, and the peak area of the benzene ring is 2.743. Therefore, the content index of the NCO functional group is A0=10.51.
[0039] (2) Determine the test section: Based on the Marshall test, determine the location where the specimen is damaged; in this embodiment, Figure 2 As shown, the first section A, the second section B and the third section C are selected as test sections, wherein the second section is the middle section of the specimen, the first section A and the third section C are symmetrical about the second section B, and the spacing between the first section A and the third section C and the second section B is in the range of about 1.0 cm.
[0040] (3) Determine the test point: Split at the selected test section to obtain the test section. Each test section must be Figure 3 As shown in the figure, test points 1-9 are selected, and A1, A2, A3, H1, H2 and H3 are the four equal lines in the horizontal and vertical directions of the Marshall specimen. In the actual evaluation process, it is necessary to ensure that each test point is located at the polyurethane adhesive position to exclude interference from materials such as stones; taking the evaluation of the curing degree of the second section B in the middle of the specimen as an example, 3 test points are selected in the horizontal and vertical directions of the test section, respectively, as shown in the figure below: Figure 3 As shown, the test points should be selected in the polyurethane adhesive area as much as possible.
[0041] (4) Sampling was performed at the selected test points, KBr tablets were pressed and Fourier infrared evaluation was performed. The infrared spectrum was obtained and the peak area corresponding to the characteristic functional group was calculated based on the infrared spectrum. Specifically, the characteristic functional group of polyurethane is the NCO group, and the peak transmittance of this group in the FTIR spectrum is located at 2270 cm -1 , so we choose 2420 cm -1 -2120 cm -1 The peak area of the NCO functional group was calculated in the vicinity, and the results are shown in Table 1.
[0042] (5) Calculate the content index A of the characteristic functional group. Since polyurethane materials contain benzene rings, and the content of benzene rings is relatively stable, the peak area ratio method is used to calculate the content index of the NCO functional group. That is, the ratio of the peak area of the NCO functional group to the peak area of the benzene ring is the content index A of the NCO functional group. The peak of the benzene ring is located at 1596 cm -1 The results of NCO functional group content index A are shown in Table 1.
[0043] (6) Evaluation of single-point curing degree: Substitute the content index A of the above characteristic functional groups into formula (1), The curing degree of a single point = (1-A1 / A0)*100% (1), Wherein, A0 represents the content index of the initial functional group of the polyurethane adhesive when it is not cured; A1 represents the content index of the functional group at the evaluation time after the polyurethane adhesive begins to cure; the curing degree of each single point is calculated, and the calculation results are shown in Table 1.
[0044] (7) Evaluate the degree of solidification of a single cross section. The overall degree of solidification of the cross section is calculated using the average value of the nine points as the final evaluation standard. The same calculation method is used for other cross sections. The overall degrees of solidification of the three cross sections are respectively referred to as L1, L2, and L3. The calculation results are shown in Table 1. It can be seen that L1 = 97.22%, L2 = 88.58%, and L3 = 91.18%.
[0045] Table 1 NCO functional group content index and curing degree results of test points and test sections
[0046] (8) In order to reduce the error of the curing process of the polyurethane mixture and evaluate the overall curing degree of the specimen, firstly, the average curing degree of the L1 and L3 sections is calculated as L 13 =95.44%, then calculate L2 and L 13 The average degree of curing is 93.31%, so the degree of curing of the polyurethane mixture described in this embodiment is 93.31%.
[0047] Example 2 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, and the following steps are performed in sequence.
[0048] (1) Prepare a polyurethane mixture with an AC-16 grading and a Marshall specimen, and take the mixture for Fourier infrared evaluation before curing to obtain an infrared spectrum. The characteristic functional group of polyurethane is the NCO group, and the peak transmittance of this group in the FTIR spectrum is located at 2270 cm -1 , so we choose 2420 cm -1 -2120 cm -1 The peak area of the NCO functional group is calculated in the vicinity; the peak of the benzene ring is located at 1596cm -1 When the material is not cured, the peak area of the NCO functional group is 33.152, and the peak area of the benzene ring is 7.157. Therefore, the content index of the NCO functional group is A0=4.632.
[0049] (2) Determine the test section and determine the location where the specimen is damaged based on the Marshall test. In this embodiment, Figure 2 As shown, the first section A, the second section B and the third section C are selected as test sections, wherein the second section is the middle section of the specimen, the first section A and the third section C are symmetrical about the second section B, and the spacing between the first section and the third section and the second section is preferably about 1.5 cm.
[0050] (3) Determine the test point: Split at the selected test section to obtain the test section. Each test section must be Figure 3 As shown, test points 1-9 are selected. A1, A2, A3, H1, H2 and H3 are the horizontal and vertical quarter lines of the Marshall specimen. In the actual evaluation process, it is necessary to ensure that each test point is located at the polyurethane adhesive position to exclude interference from materials such as stone. Taking the evaluation of the curing degree of the second section B in the middle of the specimen as an example, 3 test points are selected in the horizontal and vertical directions of the test section, as shown in Figure 1. Figure 3 As shown, the evaluation points should be selected in the polyurethane adhesive area as much as possible.
[0051] (4) Sampling was performed at the selected test points, KBr tablets were pressed and Fourier infrared evaluation was performed. The infrared spectrum was obtained and the peak area corresponding to the characteristic functional group was calculated based on the infrared spectrum. Specifically, the characteristic functional group of polyurethane is the NCO group, and the peak transmittance of this group in the FTIR spectrum is located at 2270 cm -1 , so we choose 2420 cm -1 -2120 cm -1 The peak area of the NCO functional group was calculated in the vicinity, and the results are shown in Table 2.
[0052] (5) Calculate the content index A of the characteristic functional group. Since polyurethane materials contain benzene rings, and the content of benzene rings is relatively stable, the peak area ratio method is used to calculate the content index of the NCO functional group. That is, the ratio of the peak area of the NCO functional group to the peak area of the benzene ring is the content index A of the NCO functional group. The peak of the benzene ring is located at 1596 cm -1 The results of NCO functional group content index A are shown in Table 2.
[0053] (6) Evaluation of single-point curing degree: Substitute the content index A of the above characteristic functional groups into formula (1), The curing degree of a single point = (1-A1 / A0)*100% (1) Wherein, A0 represents the content index of the initial functional group of the polyurethane adhesive when it is not cured; A1 represents the content index of the functional group at the evaluation time after the polyurethane adhesive begins to cure; the curing degree of each single point is calculated, and the calculation results are shown in Table 2.
[0054] (7) Evaluate the degree of solidification of a single cross section. The overall degree of solidification of the cross section is calculated using the average value of the nine points as the final evaluation standard. The same calculation method is used for other cross sections. The overall degrees of solidification of the three cross sections are respectively referred to as L1, L2, and L3. The calculation results are shown in Table 2. It can be seen that L1 = 91.42%, L2 = 87.45%, and L3 = 78.44%.
[0055] Table 2 NCO functional group content index and curing degree results of test points and test sections
[0056] (8) In order to reduce the error of the curing process of the polyurethane mixture and evaluate the overall curing degree of the specimen, firstly, the average curing degree of the L1 and L3 sections is calculated as L 13 =83.27%, then calculate L2 and L 13 The average degree of curing is 85.36%, so in this embodiment, the overall degree of curing of the evaluated specimen is 85.36%.
[0057] Example 3 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that, in step (3), three test points are selected for each cross section, specifically: Figure 3 The single point curing degree was calculated at the 4th, 5th and 6th points shown in Table 3.
[0058] Table 3 NCO functional group content index and curing degree results of test points and test sections
[0059] After calculation, L 13 =96.17%, L 123 =93.64%.
[0060] Example 4 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that, in step (3), 6 test points are selected for each cross section, namely Figure 3 The single point curing degree is calculated for points 1-3 and 7-9. The results are shown in Table 4.
[0061] Table 4 NCO functional group content index and curing degree results of test points and test sections
[0062] After calculation, L 13 =95.07%, L 123 =93.14%.
[0063] Example 5 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (3), four test points are selected for each cross section, namely Figure 3 The single-point curing degree is calculated for points 1, 3, 7, and 9, and the results are shown in Table 5.
[0064] Table 5 NCO functional group content index and curing degree results of test points and test sections
[0065] After calculation, L 13 =95.37%, L 123 =93.30%.
[0066] Example 6 This embodiment provides a quantitative test method for the degree of curing of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), two test sections are selected, namely the first section and the third section, and 9 points are selected in each section to evaluate the single-point curing degree. The results are shown in Table 6.
[0067] Table 6 NCO functional group content index and curing degree results of test points and test sections
[0068] The average value of the overall curing degree of the two sections is taken as the curing degree of the polyurethane mixture, which is 95.44%.
[0069] Example 7 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), two test sections are selected, namely, the first section and the third section, and in step (3), three points are selected for each section, namely Figure 3 The single point curing degree was evaluated at points 4-6 in the test. The results are shown in Table 7.
[0070] Table 7 NCO functional group content index and curing degree results of test points and test sections
[0071] The average of the overall curing degree of the two cross sections was taken as the curing degree of the polyurethane mixture, which was 96.17%.
[0072] Example 8 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), one section is selected for evaluation, namely, the second section in the middle, and in step (3), three test points are selected on the section, namely, Figure 3 The single point curing degree was calculated at the 4th, 5th and 6th points shown in the figure. The results are shown in Table 8.
[0073] Table 8 NCO functional group content index and curing degree results of test points and test sections
[0074] That is, the curing degree of the polyurethane mixture is 91.12%.
[0075] Example 9 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), one section is selected for evaluation, namely, the second section in the middle, and in step (3), 9 test points are selected on the section, specifically: Figure 3 The single point curing degree was calculated at the points 1-9 shown in Table 9.
[0076] Table 9 NCO functional group content index and curing degree results of test points and test sections
[0077] That is, the curing degree of the polyurethane mixture is 91.18%.
[0078] Example 10 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (3), 5 points are selected for evaluation on each cross section, namely Figure 3 The points are 1, 3, 5, 7, and 9. The results are shown in Table 10.
[0079] Table 10 NCO functional group content index and curing degree results of test points and test sections
[0080] After calculation, L 13 =95.73%, L 123 =93.06%, the curing degree of the polyurethane mixture is 93.06%.
[0081] Embodiment 11 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), the first section and the third section are selected as test sections, and in step (3), 5 points are selected for evaluation on each section, namely Figure 3 The points are 1, 3, 5, 7, and 9. The results are shown in Table 11.
[0082] Table 11 NCO functional group content index and curing degree results of test points and test sections
[0083] After calculation, L 13 =95.73%, which is the degree of curing of the polyurethane mixture.
[0084] Example 12 This embodiment provides a quantitative test method for the curing degree of a road polyurethane mixture, which is basically the same as that of Embodiment 1, except that in step (2), the second section in the middle is taken as the test section, and in step (3), 5 points are selected on the section for evaluation, namely Figure 3 The points are 1, 3, 5, 7, and 9. The results are shown in Table 12.
[0085] Table 12 NCO functional group content index and curing degree results of test points and test sections
[0086] That is, the curing degree of the polyurethane mixture is 90.39%.
[0087] Example 13 This embodiment provides a quantitative test method for the curing degree of road-use polyurethane mixture, which is basically the same as that of Embodiment 1. The only difference is that in step (2), the first cross-section and the second cross-section are selected as the test cross-sections, and in step (3), 5 points are selected for evaluation on each cross-section, that is Figure 3 points 1, 3, 5, 7, and 9 in
[0088] Table 13 Content index of NCO functional group and curing degree results of test points and test cross-sections
[0089] The average value is taken as the curing degree of the polyurethane mixture, that is, 93.86%.
[0090] Embodiment 14 This embodiment provides a quantitative test method for the curing degree of road-use polyurethane mixture, which is basically the same as that of Embodiment 1. The only difference is that in step (2), the second cross-section and the third cross-section are selected as the test cross-sections, and in step (3), 5 points are selected for evaluation on each cross-section, that is Figure 3 points 1, 3, 5, 7, and 9 in
[0091] Table 14 Content index of NCO functional group and curing degree results of test points and test cross-sections
[0092] The average value is taken as the curing degree of the polyurethane mixture, that is, 92.26%.
[0093] Comparative Example 1 This comparative example provides a quantitative test method for the curing degree of road-use polyurethane mixture, which is basically the same as that of Embodiment 1. The only difference is that four specimens are selected and the cross-section of the split specimen is observed by the empirical method. As Figure 4 shown, only the overall curing degree of the polyurethane mixture can be analyzed by the cross-section color as a < b < c < d, and quantitative analysis cannot be carried out.
[0094] Comparative Example 2 This comparative example provides a quantitative test method for the curing degree of road-use polyurethane mixture, which is basically the same as that of Embodiment 1. The only difference is that the cross-section of the split specimen is observed by the empirical method. Figure 5 As shown, only the overall curing degree of the polyurethane mixture can be analyzed to be relatively high by the cross-section color, and quantitative analysis cannot be carried out. Moreover, the color at the top of the mixture is lighter, indicating a higher curing degree, and the color at the bottom is darker, indicating a lower curing degree at the bottom, and other quantitative analyses cannot be carried out.
[0095] The color of the polyurethane mixture gradually becomes lighter as the degree of curing increases. Figure 5 As shown, the degree of curing of the polyurethane mixture can be evaluated by observing its color, but this method mainly relies on experience. It is difficult to observe subtle changes in color with the naked eye, so it is difficult to accurately evaluate the degree of curing.
[0096] Comparative Example 3 This comparative example provides a quantitative test method for the degree of curing of a road polyurethane mixture, which is basically the same as Example 1, except that a mechanical method is used to quantitatively evaluate the degree of curing of the polyurethane mixture, and it is found that the stability of a general polyurethane mixture ultimately fluctuates around 150KN.
[0097] In this comparative example, the mechanical method was used to conduct a stability test on the specimen, and the relationship between the curing time and the stability was obtained as shown in the figure below. Figure 6 As shown, based on Figure 6 and one The stability of the general polyurethane mixture eventually fluctuates around 150KN. The curing degree of the polyurethane mixture is converted for quantitative analysis to obtain the specific curing degree. Figure 7 shown.
[0098] The empirical method is used to judge the curing degree of polyurethane mixture, and quantitative analysis cannot be performed; the mechanical method is used to evaluate the curing degree of polyurethane mixture. Since the specimen needs to be destroyed in each experiment, if the curing degree of polyurethane mixture is found to be low or incomplete or unsatisfactory or does not meet the requirements, it can only be started from the beginning, Marshall specimens are prepared, cured for a longer time, and mechanical experiments are conducted again. This leads to the problem of low efficiency and long cycle in evaluating the curing degree of polyurethane mixture by mechanical method. Polyurethane mixture is composed of materials such as stone, adhesive and mineral powder. Factors such as gradation and raw materials will affect the curing characteristics and mechanical properties of the mixture. Polyurethane mixture has its own independent characteristics under each mix ratio condition. When factors such as gradation change, when using the mechanical method for evaluation, it is necessary to conduct experiments from the beginning for evaluation, and the applicability of this method is poor. As the curing time of polyurethane mixture increases, the mechanical strength gradually increases, but the stability of polyurethane mixture may not stop growing after 40 days of curing. This method takes a long time and the data stability is poor, which also makes it difficult for the mechanical method to accurately judge the curing degree of polyurethane mixture. Moreover, the mechanical method for judging the curing degree of the polyurethane mixture needs to convert the stability value into the curing degree, which cannot achieve a direct quantitative and accurate assessment of the curing degree of the polyurethane mixture.
[0099] In summary, the quantitative testing method of the present invention can directly and quantitatively analyze the curing degree of the polyurethane mixture without the need for further conversion, etc., which can improve efficiency to a certain extent.
[0100] The quantitative test method of the present invention is essentially to evaluate the curing degree of the polyurethane mixture by reducing the relative content of the NCO functional group based on the benzene ring. Therefore, common methods that can quantitatively obtain the content of the NCO functional group and the content of the benzene ring can be used, such as nuclear magnetic resonance spectroscopy (NMR) and infrared spectroscopy (FTIR), but the content of the NCO functional group and the content of the benzene ring need to be obtained by the same method to improve the accuracy of the results and avoid errors caused by different characterization methods. Therefore, although the present invention is only illustrated by Fourier infrared spectroscopy evaluation, those skilled in the art can also expect that other common methods that can quantitatively obtain the content of the NCO functional group and the content of the benzene ring can be applicable.
[0101] The quantitative testing method provided by the present invention is based on the curing reaction mechanism of the polyurethane mixture. Since the polyurethane material contains the NCO characteristic functional group, the content of the NCO functional group will gradually decrease with the increase of the curing degree. Therefore, with the help of Fourier infrared spectroscopy technology and other means, a testing method for the curing degree of the polyurethane mixture is proposed from the curing reaction mechanism level, and the curing degree of the polyurethane material is evaluated by the reduction of the NCO group. However, due to equipment errors, simply calculating the peak area of the NCO functional group may produce a large error. Therefore, the content index of the characteristic functional group is proposed by the peak area ratio method, and the current content of the NCO functional group is reflected by calculating the ratio of the peak area of the NCO functional group to the peak area of the benzene ring. At the same time, considering that the polyurethane mixture may have the problem of uneven curing degree, combined with the stress characteristics of the Marshall stability test, it is preferred to select three sections in the middle and left and right sides of the specimen. The section spacing should be adjusted according to the grading. The adjustment principle is that the larger the grading, the larger the section spacing. The curing degree of the three sections is evaluated respectively, and the overall curing degree of the polyurethane mixture is obtained on this basis. This quantitative test method can achieve the purpose of horizontal comparison of different evaluation results, thereby improving the applicability and accuracy of the quantitative test method.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quantitative test method for the curing degree of a road polyurethane mixture, characterized in that: The method includes obtaining the content of NCO functional groups and the content of benzene rings in the polyurethane mixture, and taking the relative content of NCO functional groups to benzene rings in the polyurethane mixture as the content index A of the NCO functional groups. The curing degree of the road polyurethane mixture is calculated by the following formula: Formula (1), Wherein, A0 represents the content index of the initial NCO functional group of the road polyurethane mixture before curing; A1 represents the content index of the NCO functional group at the testing moment after the road polyurethane mixture starts to cure.
2. The testing method according to claim 1, characterized in that: Includes steps: (1) Determine the test section and, based on the Marshall test, determine the location where the specimen fails, which is the location of the test section farthest from the center section of the specimen; (2) Selecting test points on the test section; (3) Sampling is performed at each test point for analysis to obtain the content of NCO functional groups and the content of benzene rings; (4) Calculate the curing degree of each test point using formula (1); (5) Calculate the overall degree of curing for each test section; (6) Calculate the degree of curing of the specimen.
3. The testing method according to claim 2, characterized in that: In step (1), the central section of the specimen is taken as the second section, and at least three sections are selected as test sections, wherein the at least three sections include the second section and the test sections on both sides thereof; preferably, the test sections on both sides of the second section are symmetrically distributed about the second section.
4. The testing method according to claim 3, characterized in that: The spacing between adjacent test sections was 0.5-2.5 cm.
5. The testing method according to claim 3 or 4, characterized in that: Select 3-7 test sections, preferably 3-5 test sections.
6. The testing method according to claim 5, characterized in that: The number of the test sections is an odd number.
7. The testing method according to any one of claims 2 to 6, characterized in that: In step (2), the test point is selected in the polyurethane adhesive area.
8. The testing method according to claim 7, characterized in that: 3-9 test points are selected from each of the test sections; preferably, 4-9 test points are selected from each of the test sections; more preferably, 6-9 test points are selected from each of the test sections.
9. The testing method according to any one of claims 2 to 8, characterized in that: In step (5), the average value of all test points of each test section is calculated and recorded as the overall curing degree of the test section as L n , n corresponds to the test section name; And / or, in step (6), firstly calculate the average degree of solidification of the test cross sections symmetrically distributed about the second cross section, denoted as L nn If a test section does not have a symmetrical test section, its overall curing degree L n Denoted as L fn ; where n corresponds to the name of the test section; then, calculate L2, L nn , L fn The average value of is taken as the final curing degree of the road polyurethane mixture.
10. The testing method according to any one of claims 1 to 9, characterized in that: The content of NCO functional groups and benzene rings in the road polyurethane mixture is obtained by a quantitative analysis method; Preferably, the quantitative analysis method is selected from any one of nuclear magnetic resonance spectroscopy and infrared spectroscopy.